Anterior colporrhaphy plus inside‐out tension‐free vaginal tape for associated stress urinary incontinence and cystocele: 10‐year follow up results. Issue 3 (23rd October 2017) - Montera, Roberto; Miranda, Andrea; Plotti, Francesco; Terranova, Corrado; Luvero, Daniela; Capriglione, Stella; Scaletta, Giuseppe; Zullo, Marzio A.; Buscarini, Maurizio; Lopez, Salvatore; Gatti, Alessandra; Schirò, Teresa; et al.
Abstract : Aims: We report the success rate and complications rate of combined ultralateral anterior Colporrhaphy plus Tension‐free Vaginal Tape (TVT‐O) in a long‐term (10 year) follow‐up prospective survey. Methods: Patients previously treated for associated stress urinary incontinence (SUI) and cystocele were subjected to annual follow‐up for 10 year with a complete urogynecologic evaluation. Furthermore, an urodynamic assessment and a quality of life questionnaire (ICIQ‐UI SF) were recorded at the 5th and 10th year of follow up. Results: Fifty patients treated between June 2004 and May 2006 were included in the analysis. Five patients did not return to 5‐yr follow‐up: two patients developed a median tape erosion and three patients withdraw. At 10‐yr follow‐up two more patients withdraw for a total of seven patients lost to follow‐up. After 10 years patients objectively cured from cystocele were 41 (95%) while patients objectively cured from SUI were 39 (91%). At 10th year follow‐up 38 patients (89%) result cured from both SUI and cystocele, 3 (7%) patients result cured only from prolapse, 1 (2%) patient only from SUI, and 1 (2%) patient result objectively failed for both SUI and cystocele. The ICIQ‐UI SF scores at 10th year follow‐up was 6.2 ± 3.7. The late complication rate at 10th year follow‐up was 32% (OAB symptoms 20%; Mixed incontinence 2%; Bladder outlet obstruction 0%; Dyspareunia 6%; Chronic pelvic pain 0%; Vaginal tape erosion 4%; Detrusor hyperactivity 0%). Conclusions: The combined procedures shown proved to be an effective and safe procedure to treat concomitant SUI and cystocele.